COVID-19 and price stability in Eastern Africa: How effective were the governments' policy response measures? - Cyprian Amutabi (Cogent Economics & Finance, 2022)
This study used monthly panel data for the period March 2020-April 2021 in analyzing the differences in the impact of the COVID-19 pandemic on price stability in the East Africa Community (EAC) region. We also sought to establish the effectiveness of the governments' policy response measures in maintaining price stability. Estimates from the Pooled Mean Group (PMG) model revealed evidence of a long-run relationship between COVID-19 and the Consumer Price Index (CPI) in the EAC region. Secondly, COVID-19 significantly increased the CPI across the panel in the long run. In the short run, the impact was significant and positive for Kenya but negative for Rwanda and South Sudan. The question of whether government policy response measures were indeed effective in maintaining price stability posits a dilemma that is rather reminiscent of a paradoxical policy solution. On one hand, governments are concerned with the welfare of their citizens which was worsened by the inception of the pandemic, and thus roll out relief measures to help inject liquidity into businesses and households. Conversely, governments are also wary that their actions might actually increase the money supply and thus trigger inflation. Governments, therefore, need to step up their vaccination drive as this is critical in spearheading the economies' re-opening and, thus, recovery in the long run. This is contrary to the long-term application of the relief measures. Further, governments within the region need to develop well-managed food reserves that can provide a cushion in the event of price fluctuations emanating from the effects of such economic shocks.
Keywords: 330; COVID-19; CPI; PMG model; policy response measures; EAC region